KARAKTERISASI SIFAT MEKANIK STRUKTUR SANDWICH DAN MATERIAL PENYUSUNNYA MELALUI PENGUJIAN BENDING DENGAN VARIASI PANJANG PENUMPU - Hernaning Tias, Etty
Sandwich structure consists of thin skin and thick core. Skin material has high mechanical properties, while core material has low density. Sandwich structure has compound properties of the constituent materials, that is high mechanical properties with low density. Flexural test with span length variations is used to determine mechanical properties of sandwich and its constituent materials. Flexural test in the elastic region is used to result the stiffness of sandwich and its constituent materials. The strength of the constituent materials is determined by flexural test until the specimen failed at the skin or the core. Furthermore, mechanical properties resulted from flexural test were compared with results of composite tensile test and analytical computation. The characterization of mechanical properties of sandwich, core, and skins has been done at two samples, which are FRP with balsa wood core and FRP+aluminium with divinycell core. Sandwich bending stiffness, sandwich shear stiffness, core shear stiffness, skin normal stiffness, skin strength, and core shear strength were determined by flexural test with span length variations. However????there are factors that need to be considered to determine the mechanical properties of sandwich and its constituent materials, that are failure mechanism, resin between finite block core material, and localized load in flexural test.